Greywater adsorption into soil during irrigation - A. H. M. Faisal Anwar; Upaka Rathnayake; Will Bowyer (Applied Water Science, 2022)
Abstract The reuse of greywater has significant potential to reduce the demand on potable water. The greywater produced from laundry is free from oil and grease and hence makes it attractive to reuse for irrigation. This study investigates the adsorption of surfactant-rich laundry greywater into the soil surfaces during irrigation. A series of miscible displacement column experiments was conducted under water-saturated condition using non-reactive (NaCl solution of concentration 0.650 g/L) and reactive tracers (greywater solution of concentration 0.26–0.442 g/L with same background electrolyte). Plasterer’s sand was used as the porous medium. Samples collected at the column outlet every two minutes were measured for pH, electrical conductivity and greywater concentrations. Hydraulic conductivity for each experiment was also determined using constant head method. Separate experiments were conducted to determine the surface tension of greywater solution (with same background electrolyte) and modelled using Gibbs adsorption isotherm. Surface tension of greywater reduces with increasing greywater concentration and becomes constant at greywater concentration of 0.440 g/L. The results revealed that pH is improved and electrical conductivity decreased indicating it may increase the soil salinity. The comparison of breakthrough curves of reactive and non-reactive tracers showed that the greywater adsorptions occur into the soil surfaces and it increased with greywater concentrations, which may make the soil water-repellent. This may be a concern if soil becomes water-repellent, increases hydraulic conductivity and enhances the risk of groundwater pollution. The concentration of greywater needs to be checked before irrigation and if needed, it should be diluted to avoid any risk of soil water-repellence.